ChemInform Abstract: Chiral Auxiliary Induced Diastereoselective Synthesis of (R, R)‐N, N′‐Di(tert‐butoxycarbonyl)cyclohex‐4‐ene‐1, 2‐diamine. Issue 18 (May 2015) - Balestri, Davide; Grilli, Stefano; Romano, Ciro; Savoia, Diego
Abstract The synthesis of the title compound (VI) is based on the highly diastereoselective addition of allylzinc bromide to bisimine (I) and ring‐closing metathesis as the key steps.